Spinal cord stimulation for refractory pericarditis: a case report and a review of the mechanism of action - Elsliger, Simon; Saucier, Jacob; Schneider, Andre; El Helou, Antonios (Frontiers in Pain Research, 2023)
Background and objectives In recent years, spinal cord stimulation (SCS) has emerged as a promising management option for chronic pain of multiple etiologies. While its effectiveness has been strongly suggested in many patients, the exact mechanism of action of SCS is incompletely understood. This article reviews the leading mechanisms underlying the analgesic and cardiovascular effects of SCS and reports its novel benefits in a case of recurrent pericarditis. Literature review Throughout history, the analgesic properties of SCS were thought to arise via stimulation of the spinothalamic tract. Although this mechanism has been thoroughly reported, new research and patient outcomes from SCS have revealed various additional properties that cannot be fully explained by this mechanism alone. Evidence suggests that SCS enhances calcitonin gene-related peptide release and modulates inflammatory cytokine secretion, sympathetic tone, and inhibitory neurotransmitter secretion. These distinct mechanisms likely collectively contribute to the therapeutic effects of SCS on the cardiovascular system and pain management. Case report We report the case of a 48-year-old male patient with recurrent pericarditis, characterized by refractory angina-like pain and reduced left ventricular ejection fraction (LVEF). After 1 year of having a spinal cord stimulator implanted, the patient is free from pain and narcotics, with a reduction of 428 mg equivalent dose of morphine. The patient's LVEF increased from 40% to 45% without changes to his previous medical treatment. This is the first reported case of refractory pericarditis managed with spinal cord stimulation. Conclusion Recognizing the improved pain management, reduced narcotic usage, and improved LVEF in our patient following SCS is critical to paving the way toward a complete understanding of the mechanism of action of SCS. This case reveals the therapeutic potential of SCS for cardiovascular pathologies other than refractory angina pectoris.